2014
DOI: 10.1155/2014/769296
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Reaction Response Time between Hand and Foot Controlled Devices in Simulated Microsurgical Testing

Abstract: Purpose. We hypothesized that reaction times (RTs) for a switch release are faster for hand-controlled than for foot-controlled switches for physiological and anatomical reasons (e.g., nerve conduction speed). The risk of accidental trauma could be reduced if the surgeon reacted quicker and therefore improve the surgical outcome. Method. We included 47 medical professionals at USC. Demographics and handedness were recorded. Under a microscope, a simple reaction time test was performed, testing all extremities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 8 publications
1
25
1
1
Order By: Relevance
“…Since the conduction velocity in the motor pathways and peripheral nerves can reach several tens of meters per second, RT may slightly increase if the response requires distal body segments. Under the conditions of hand and foot contact with the timer, Pfister et al (2014) reported a significant difference between hand and foot simple RT of about 10 ms, mean data being 318 and 329 ms, respectively. Removing the delay separating foot RT from hand RT can eliminate this difference.…”
Section: Discussionmentioning
confidence: 88%
“…Since the conduction velocity in the motor pathways and peripheral nerves can reach several tens of meters per second, RT may slightly increase if the response requires distal body segments. Under the conditions of hand and foot contact with the timer, Pfister et al (2014) reported a significant difference between hand and foot simple RT of about 10 ms, mean data being 318 and 329 ms, respectively. Removing the delay separating foot RT from hand RT can eliminate this difference.…”
Section: Discussionmentioning
confidence: 88%
“…The same is true for operating the foot pedal. Furthermore, reaction times are approximately 10ms slower for feet than for hands (Pfister et al, 2014). Therefore, the timing of urge intensity and mental compulsions in the range of seconds should be regarded with some caution and the results should be confirmed in an independent study.…”
Section: Evaluation Of the Real-time Urge Monitor And Limitations Of mentioning
confidence: 93%
“…We propose tracking the foot movements for controlling the displacements of the third hand. Foot pedals are widely used for vitrectomy in microsurgery [ 33 ] and laparoscopic surgery, dentistry, etc. for turning on/off a device, as well as for commanding the endoscope movements in laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%